Strategi Pendidikan Unggul Berbasis Organisasi di Pimpinan Daerah Ikatan Pelajar Muhammadiyah Ponorogo - Sri Wahyuni; Nuraini Nuraini; Nurul Abidin (ISTAWA, 2019)
An organization-based superior education strategy is certainly very different from the formal education strategy in general. An organization-based superior education strategy is not limited by space and time. Education can be done anywhere, anytime, and how things are. So PD IPM Ponorogo seeks to maximize the superior education strategy to cadre its members so that later they can become the next generation of the nation that is useful for themselves, the community, and the nation. The purpose of this study is 1) To find out the forms of superior education, 2) To find out the organization-based superior education strategy and, 3) To understand the supporting and inhibiting factors of superior education based strategies organization in the Regional Leadership of the Muhammadiyah Ponorogo Student Association. This research approach is a qualitative approach, with a type of case study research. Data collection techniques through interviews, observation, and documentation. The results showed that the Regional Leaders of the Muhammadiyah Ponorogo Student Association had and implemented several types of education strategies namely holding positive activities, cooperating with other parties, cooperating with AUM or the institutions needed, introducing and getting used to reading books, introducing culture literacy, balancing physical and spiritual health, building an organization with family, sharing with friends, approaching members, and identifying opportunities.